Acoustic emission sensor network based fault diagnosis of induction motors using a gabor filter and multiclass support vector machines - Islam, Md Rashedul; Uddin, Jia; Kim, Jongmyon (© 2016 Old City Publishing, Inc., 2018)
This article was published in the Ad-Hoc and Sensor Wireless Networks [© 2016 Old City Publishing, Inc.]